Peningkatan Pengetahuan dan Sikap Pekebun Melalui Penyuluhan Pencegahan Ganoderma pada Tanaman Kelapa Sawit - Fanisa Afni Widitia; Rahmi Eka Putri; Hadi Wijoyo (Universitas Pahlawan Tuanku Tambusai, 2026)
Basal stem rot disease caused by Ganoderma boninense is one of the main diseases in oil palm plants that can reduce productivity and even cause plant death. The low knowledge and attitude of smallholders regarding Ganoderma prevention is one of the factors that accelerate the spread of the disease in smallholder plantations. This research activity aims to improve the knowledge and attitudes of smallholders through extension activities regarding Ganoderma prevention in oil palm plants. This research was conducted in Sumber Harapan Village, Tinggi Raja District, Asahan Regency, targeting oil palm smallholders. The method used was Rapid Rural Appraisal (RRA) through interviews, observations, and discussions with smallholders. Extension activities were carried out using demonstration methods and visits with the help of extension media in the form of leaflets. Evaluation was carried out to measure the level of knowledge through the results of pretests and posttests before and after extension calculated using the N-Gain formula. The results showed that extension activities were able to increase the knowledge of smallholders by 77.3% and improve their attitudes in implementing Ganoderma prevention in oil palm plants. Farmers have become more aware of the symptoms of Ganoderma attacks and preventative measures to suppress the spread of the disease. Therefore, outreach activities can be an effective way to increase farmer capacity in controlling Ganoderma disease in oil palms.